Electroacupuncture attenuates inflammatory pain via peripheral cannabinoid receptor type 1 signaling pathway in mice. - Tsung-Jung Ho; Ching-Fang Lin; Jhong-Kuei Chen; Yen-Lun Kung; Li-Kung Wu; Chen-Ying Chang Chien; Chun-Ping Huang (PLoS ONE, 2023)
Pain is strongly associated with neuro-immune activation. Thus, the emerging role of the endocannabinoid system in neuro-inflammation is important. Acupuncture has been used for over 2500 years and is widely accepted for the management of pain. Our study aimed to investigate the effects of electroacupuncture on the regulation of cannabinoid receptor type 1 within the peripheral nervous system. Inflammatory pain was induced by injecting Complete Freund's adjuvant to induce mechanical and thermal hyperalgesia. Electroacupuncture significantly attenuated the mechanical and thermal sensitivities, and AM251, a cannabinoid receptor type 1 antagonist, eliminated these effects. Dual immunofluorescence staining demonstrated that electroacupuncture elevated expression of cannabinoid receptor type 1, co-localized with Nav 1.8. Furthermore, electroacupuncture significantly reduced levels of Nav 1.8 and COX-2 by western blot analysis, but not vice versa as AM251 treatment. Our data indicate that electroacupuncture mediates antinociceptive effects through peripheral endocannabinoid system signaling pathway and provide evidence that electroacupuncture is beneficial for pain treatment.